Penerapan Model Pembelajaran Mind Mapping untuk Meningkatkan Keaktifan Siswa - Imron, Ali; Mahfudhoh, Aimmatul (TARBAWIYAT, 2024)
Quality education depends not only on the material taught, but also on the way it is delivered. One of the main challenges in the learning process is keeping students active and engaged. Student activeness is important as it can improve their understanding, thinking skills and creativity. However, many students tend to be passive in learning. To overcome this, more innovative and interactive methods are needed, one of which is Mind Mapping. Mind Mapping is a visual organisation of ideas technique that helps students understand complex concepts, plan tasks, and connect information. The application of Mind Mapping in class IV can have a significant impact in increasing student activeness by stimulating creative and critical thinking. This article discusses the application of Mind Mapping as an effort to increase the activeness of grade IV students, including the basic concepts, how to apply it in learning, as well as the benefits and challenges faced by teachers and students. The use of Mind Mapping not only makes it easier for students to organise and recall information, but also enhances collaboration, creativity and learning independence. However, challenges such as difficulty in explaining concepts to students and limited creativity need to be overcome to maximise the effectiveness of this method.